# Prove that if $AB$ is invertible then $B$ is invertible.

I know this proof is short but a bit tricky. So I suppose that $AB$ is invertible then $(AB)^{-1}$ exists. We also know $(AB)^{-1}=B^{-1}A^{-1}$. If we let $C=(B^{-1}A^{-1}A)$ then by the invertible matrix theorem we see that since $CA=I$(left inverse) then $B$ is invertible. Would this be correct?

Edit Suppose $AB$ is invertible. There exists a matrix call it $X$ such that $XAB=I$. Let $C=XA$ Then $CB=I$ and it follows that $B$ is invertible by the invertible matrix theorem.

• You're assuming your conclusion when you write that $(AB)^{-1}=B^{-1}A^{1}$. – JSchlather Aug 3 '13 at 20:30
• The equation $(AB)^{-1} = B^{-1}A^{-1}$ presumes the existence of both $A^{-1}$ and $B^{-1}$. – Sangchul Lee Aug 3 '13 at 20:31
• Are $A,B$ square matrices or do we only assume that $AB$ is square? – Hagen von Eitzen Aug 3 '13 at 20:34
• Assume $AB$ is square. – user60887 Aug 3 '13 at 20:35
• It is not necessarily true that $(AB)^{-1}=B^{-1}A^{-1}$. – AnonSubmitter85 Aug 3 '13 at 20:35

## 8 Answers

$\;AB\;$ invertible $\;\implies \exists\;C\;$ s.t.$\;C(AB)=I\;$ , but using associativity of matrix multiplication:

$$I=C(AB)=(CA)B\implies B\;\;\text{is invertible and}\;\;CA=B^{-1}$$

• this only shows that B has a left inverse. you cannot infer that B also has a right inverse. A has a right inverse but no left inverse. Only if A or B are square you can infer that. But this is neither stated by you nor by the OP. – Andreas H. Aug 4 '13 at 2:10
• Unless otherwise stated I always assume $\;A,B\;$ are square. If the OP meant otherwise he can say. – DonAntonio Aug 4 '13 at 3:52
• Especially since the theorem is false as stated if $A,B$ are not square. A non-surjective mapping composed with a non-injective mapping can be invertible- think of embedding $\mathbb R ^2$ into $\mathbb R ^3$ and then projecting back to $\mathbb R ^2$. The corresponding matrices will be $2 \times 3$ and $3 \times 2$ and thus not invertible, but the product will be $2 \times 2$ and invertible. – Devlin Mallory Aug 4 '13 at 9:14
• Exactly @Devlin. I was about to remark that if not square a matrix can be left or right invertible yet, perhaps, not both. +1 – DonAntonio Aug 4 '13 at 9:16
• Proving B also has a right inverse is easy if we assume that $A$ is also invertible. $$(AB)C=I \implies A(BC)=I \implies A^{-1}A(BC)=A^{-1} \implies BC=A^{-1} \implies BCA=A^{-1}A \implies B(CA)=I$$ – ViX28 Jun 5 '18 at 20:53

A more basic argument, based on invertible $\iff$ nonsingular, is as follows. If $B$ were singular, there would be $x\ne 0$ with $Bx=0$, hence with $(AB)x=0$, whence $AB$ is likewise singular.

Do you have the theorem that $X$ is invertible if and only if $\det X \neq 0$?

If so, then if $AB$ is invertible, $\det AB\ne 0$. But $\det AB = \det A\cdot \det B \ne 0$, so both $\det A$ and $\det B$ are nonzero, and therefore both $A$ and $B$ are invertible.

• Yes but in a later section. – user60887 Aug 3 '13 at 20:37
• It should be $\det X \ne 0$. – Boris Novikov Aug 3 '13 at 20:47

Thanking Ted Shifrin I completely revise my answer.

You want to prove that $B$ is invertible using only semigroup properties of matrices (i.e. multiplication, associativity and existence of the unity $I$).

You had proved that $B$ has a left inverse, $CB=I$. Now it should prove that there is a right inverse, $BD=I$. However, it is not true in semigroups, generally speaking. An example: so called bicyclic monoid $S=\langle a,b| ab=1\rangle$ (it is generated by $a,b$ with the defining relation $ab=1$). In $S$ the product $ab$ is invertible (since it equals $1$), $b$ has the left inverse $a$, but has not a right inverse.

Сonclusion: To prove what you want, it is not enough to use semigroup properties. One have to use either determinants or vectors (or something else).

• Analogously? What do you have in mind? – Ted Shifrin Aug 3 '13 at 21:02
• @Ted Shifrin: Generally speaking, an element of a semigroup may have a left inverse and a right inverse, and they must not be equal. – Boris Novikov Aug 3 '13 at 21:10
• You miss the point: How do you deduce that $B$ has a right inverse? – Ted Shifrin Aug 3 '13 at 21:11
• @Ted Shifrin: You are right, thank you. I will edit the answer. – Boris Novikov Aug 3 '13 at 21:20

This might be easier to do by thinking of $A$ and $B$ as linear operators rather than by matrix arithmetic. Assume $AB$ is invertible and assume that $B$ is not. Thus, $B$ either fails to be injective or fails to be surjective. If $B$ is not injective, then there is $x,y$ with $x \neq y$ such that $Bx=By$, and hence $ABx=ABy$, and $AB$ is not injective, which is a contradiction. Now, assume that $B$ is not surjective. Thus, its image must have dimension strictly less than the dimension of its domain. (Here is where we assume $A,B$ are square.) Thus, the composition $AB$ must have an image of dimension strictly less than the dimension of the domain of $B$, and thus cannot be surjective, another contradiction. Thus $B$ is injective and surjective and thus invertible.

Take some arbitrary vector from the null space from $B$ and call this $\vec{w}$. Than $B\vec{w} = \vec{0}$ and so is $AB\vec{w} = \vec{0}$. We conclude that $\text{null}(B) \subseteq \text{null}(AB)$. Now since $AB$ is invertible we know that $\text{null}(AB) = \{ \vec{0} \}$, and therefore so is $\text{null}(B)$. Using the fundamental theorem of invertible matrices we conclude that $B$ is invertible as well.

$n=\mathrm{rank}(AB)\le\mathrm{rank}(B)$, therefore $\mathrm{rank}(B)=n$.

Let $$A,B\in M_{n\times n}(F)$$ and let $$AB$$ be invertible.

Suppose that $$B$$ is not invertible. The linear transformation $$L_B:F^n\rightarrow F^n$$, $$L_B(x)=Bx$$ is then not invertible as the matrix representation of $$L_B$$ is not invertible. However, since it is a linear transformation and the domain and codomain are each of the same finite dimension, it follows that $$L_B$$ is not injective and not surjective. As $$L_B$$ is not injective, there exists some $$x\in F^n$$ where $$L_B(x)=Bx=0$$ and $$x\neq 0$$.

However, $$Bx=0$$ means $$\left[(AB)^{-1}A\right]Bx=\left[(AB)^{-1}A\right]\cdot 0 \,\Rightarrow\, x=0$$ a contradiction. Therefore $$B$$ is invertible.

As $$AB$$ is invertible,

$$A\left[B(AB)^{-1}\right]=I_n.$$ Then $$(AB)^{-1}AB=I_n\,\Rightarrow\, (AB)^{-1}ABB^{-1}=B^{-1} \,\Rightarrow\, (AB)^{-1}A=B^{-1} \,\Rightarrow\, B(AB)^{-1}A=BB^{-1}$$ which means $$\left[B(AB)^{-1}\right]A=I_n$$ so $$A$$ is invertible.